Razón de cambio en la recaudación del Impuesto al Valor Agregado en México; Rate of change in the collection of Value Added Tax in Mexico - Sergio Lagunas Puls; Genaro Aguilar Gutiérrez (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2019)
– The objective of this paper is to identify the months in which more products and services are consumed in Mexico with the Value Added Tax (VAT), using the percentage change ratio (collection speed / month) based on the information for the year 2003 and until the month of August 2015. For each of the months of the series, the best fitting polynomial equation is obtained, using it to estimate the monthly collection and comparing these values with those obtained from the first derivative. The results show that the months of March, April and December present a greater speed in the collection / month, which represents that the effective consumption manifests itself in the months prior to this capture, in other words, the periods in which the Mexicans consume more products and services are February, March and November.
Keywords: E62; E63; C3; 330; value added tax; rate of change; fiscal system in México